1986
DOI: 10.1111/j.1398-9995.1986.tb00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Lowered Glutathione‐Peroxidase Activity in Asthmatic Patients with Food and Aspirin Intolerance

Abstract: In analogy with findings from animal experiments, people with low glutathione-peroxidase (GSH-Px) activity could be expected to have altered sensitivities to effects of drugs, chemicals and possibly food. We have investigated GSH-Px activity in 12 patients with intrinsic asthma and food and aspirin intolerance. Ten of the 12 patients had very low or low GSH-Px activity and the frequency of low GSH-Px activity in this group was statistically significant (P less than 0.001) compared with the control material of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 10 publications
5
19
0
Order By: Relevance
“…Chronic oxidative stress is permanently present in asthmatic patients [2,3]. The RBCs can be regarded as circulatory antioxidant carriers which reflect exposure to ROS [8,15]. Since RBCs are available easier than the lung tissue and play the most essential role in the antioxidant defence mechanisms, they have been used in the evaluation of the degree of oxidative stress [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic oxidative stress is permanently present in asthmatic patients [2,3]. The RBCs can be regarded as circulatory antioxidant carriers which reflect exposure to ROS [8,15]. Since RBCs are available easier than the lung tissue and play the most essential role in the antioxidant defence mechanisms, they have been used in the evaluation of the degree of oxidative stress [10].…”
Section: Discussionmentioning
confidence: 99%
“…One of the major functions of erythrocytes is to protect Hb and structural and enzymatic proteins from oxidative stress via the hexose monophosphate shunt (HMP shunt), enhancing glutathione reduction [14]. A lowered glutathione peroxidase activity can be detected in asthmatic patients with food and aspirin intolerance [15]. Decreased catalase and total glutathione syntheses, increased metHb and hemichrome levels and decreased reduced glutathione (GSH) stability have been observed in asthmatics [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In asthma, it has been shown that antioxidant levels are decreased, both in the pulmonary compartment [23,31] as well as in peripheral blood [1,12]. RBC have been used to monitor long-term alterations in antioxidant status in chronic pulmonary disorders [16,20], as well as in asthma [14].…”
Section: Discussionmentioning
confidence: 99%
“…In asthma, evidence for a disturbed oxidant±antioxidant balance has been found in the general circulation. Decreased glutathione peroxidase levels have been reported in serum, platelets and red blood cells (RBC) [12,13] and levels of selenium, a cofactor for glutathioneperoxidase, are reduced in asthmatic patients [13]. Decreased levels of catalase in RBC of asthmatic children have also been reported [14].…”
mentioning
confidence: 99%
“…In this connection it is of interest that Malmgren et al [8] have recently shown that glutathione-peroxi dase activity in whole blood of ASA-intolerant asth matics is significantly lower than that of age-and sexmatched healthy individuals. Glutathione-peroxidase is one of the most powerful free radical scavengers.…”
mentioning
confidence: 99%